IMPLEMENTATION OF LOCAL CONTENT CURRICULUM ABOUT LOCAL POTENCY IN REALIZING LOCAL BUILDING BASED ON SIDA (LOCAL INNOVATION SYSTEM OF WONOGIRI REGENCY) - Siti Supeni (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
The research aims at finding out the implementation of local content curriculum about localpotency as icon of Wonogiri Regency that can be applied in a teaching and learning process forjunior high school teachers through innovative, active, creative, and participative learningstrategy to realize local development based SIDA (Local Innovation System of Wonogiri).Techniques of collecting data use questionnaire, instruments, and observation on 100 teacherswith purposes sampling. The data is described and showed in the form of percentage, table, andgraphic. Research findings show that ability of teachers in designing a learning program is 70%in cognitive aspect, 20% in affective aspect, and 10 % in psychomotor aspect. Teaching andlearning process who runs completely related to local potency is 62% in cognitive aspect,however 38% in affective aspect is not applied yet. The teachers who conceive personal abilityand social interaction toward students, parents, colleague, and related society are 75%, however25 % of them are not. Teachers who are needed a support are 50%, but those who are not,namely 50%. Ability of teachers in a teaching and learning process, and appropriateness in usinglearning media and learning strategy is 60%, those who takes workshop of learning is 25%, andthose who do not understand innovation of learning medium is 15%. Teachers who are active toobtain learning opportunity in terms of change and innovation of learning on seminars,discussion, and training are 60%, however those who are not, namely 40%. The conclusion andrecommendation is that it needs even distribution of training and guiding to improve overallteacher competencies, namely teachers’ autonomous in improving their competencies.Key Words: Local Innovation System (SIDA), Content Curriculum as Local Potency, Junior HighSchool.